Pembelajaran Holistik, Konstektual dan Futuristik - Arsinta, Aulia; Rahman, Abdur; Rahman, Taufiqur (Lembaga Yasin AlSys, 2025)
This article discusses the importance of integrating three approaches in education: holistic, contextual, and futuristic, to prepare students for the future. Holistic learning focuses on overall individual development (intellectual, emotional, social, physical and spiritual). Contextual learning connects lesson material with students' real lives. Futuristic learning develops 21st century skills such as critical thinking and digital literacy. Although beneficial, the integration of these three approaches faces challenges such as limited resources, teacher preparedness, student participation, appropriate curriculum, cultural differences, and appropriate evaluation. The Merdeka Curriculum in Indonesia supports the implementation of this approach. Adaptation to local contexts and collaboration between parties are important to overcome challenges and realize quality education.